2020
DOI: 10.1038/s41467-020-16038-6
|View full text |Cite
|
Sign up to set email alerts
|

A RUNX2 stabilization pathway mediates physiologic and pathologic bone formation

Abstract: The osteoblast differentiation capacity of skeletal stem cells (SSCs) must be tightly regulated, as inadequate bone formation results in low bone mass and skeletal fragility, and overexuberant osteogenesis results in heterotopic ossification (HO) of soft tissues. RUNX2 is essential for tuning this balance, but the mechanisms of posttranslational control of RUNX2 remain to be fully elucidated. Here, we identify that a CK2/HAUSP pathway is a key regulator of RUNX2 stability, as Casein kinase 2 (CK2) phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 76 publications
2
48
0
1
Order By: Relevance
“…There is a decrease in CHIP expression in present of TRIM16 to slow the degradation of its substrate RUNX2, and also a compete between TRIM16 and CHIP for binding directly to RUNX2.The similar mode of regulation was observed in another study where LMCD1 protected the RUNX2 protein from SMURF1-mediated ubiquitination degradation, thereby regulating BMP signaling [48]. Recently, the CK2/HAUSP pathway was reported to be a key regulator of RUNX2 stability by a de-ubiquitination pathway [49]; Thus,a protein known as a de-ubiquitinase may exist, which can be recruited by TRIM16 to cleave K48-linked poly-ubiquitination chains from RUNX2, however, few studies have reported the de-ubiquitination of RUNX2, which need to be further explored.…”
Section: Discussionmentioning
confidence: 58%
“…There is a decrease in CHIP expression in present of TRIM16 to slow the degradation of its substrate RUNX2, and also a compete between TRIM16 and CHIP for binding directly to RUNX2.The similar mode of regulation was observed in another study where LMCD1 protected the RUNX2 protein from SMURF1-mediated ubiquitination degradation, thereby regulating BMP signaling [48]. Recently, the CK2/HAUSP pathway was reported to be a key regulator of RUNX2 stability by a de-ubiquitination pathway [49]; Thus,a protein known as a de-ubiquitinase may exist, which can be recruited by TRIM16 to cleave K48-linked poly-ubiquitination chains from RUNX2, however, few studies have reported the de-ubiquitination of RUNX2, which need to be further explored.…”
Section: Discussionmentioning
confidence: 58%
“…Germline deletion of RUNX2 (RUNX2−/−) or inhibition of its function in mice often results in reduced numbers of osteoblasts and marked inhibition of mineralized bone formation and chondrocyte maturation ( Otto et al, 1997 ; Maruyama et al, 2007 ). Therefore, stabilization of RUNX2 is an important intracellular event for both intramembrane and endochondral bone formation ( Kim J.M. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the same DUB can also target several distinct transcription factors in a cell-type-specific manner. For instance, USP7, in addition to its function in maintaining hESCs [ 110 ], has been shown to control the stability of several other cell-identity-defining and lineage-promoting transcription factors, including (1) REST in neural progenitor cells to promote their maintenance [ 163 , 164 ], (2) c-MYC in neural stem cells to promote their self-renewal [ 165 ], and (3) RUNX in skeletal stem cells to promote differentiation into osteoblasts [ 166 ]. Taken together, DUBs frequently target chromatin regulators or transcription factors in cell-type and tissue-specific contexts to control developmental cell-fate decisions.…”
Section: Mechanisms How Dubs Control Developmentmentioning
confidence: 99%